COVID-19 Crisis: Luxury and Fast Fashion Brands’ Communication and Marketing Strategies - Crespo Pereira, Verónica (2022)
This article provides a state of the art on the communication and marketing strategies that fashion brands have carried out during the period of COVID-19 confinement. For this purpose, a bibliographic review of articles that meet the aforementioned thematic and methodological criteria (content analysis) has been carried out. The results show a similarity of strategies and actions carried out by 10 luxury brands, as well as by three fast fashion brands at the beginning of COVID-19.